The Role of some Activities of Lean Supply Chain Management (LSCM) in Achieving Logistics Excellence: Exploratory study - Awso, Khairi A.; Habil ِAnna D.; Shaaban, Farsat A. (Humanities Journal of University of Zakho, 2019)
The study tries to determine the relationship between some activities of Lean supply chain management (lean procurement, lean transport, and lean storage) in achieving Logistics Excellence. Based on a set of hypotheses that states that these activities are related and affect the Logistics Excellence, the study was applied on two Companies (Coca-Cola and Pepsi Cola) for the production of beverages in the Kurdistan region / Iraq. The questionnaire was used as a main tool for data collection, (90) questionnaire were distributed to supply chain managers, logistics and first line managers, (80) of them were return and were valid for analysis, use correlation and affect tests to verify hypotheses. The results of the statistical analysis supported the hypotheses of the study and indicated the existence of correlation and affect of the lean supply chain activities in Logistics Excellence, the researchers propose further studies in the future on the subject to support and enhance the results of this study.The contribution of the current study comes from the support of the researched companies for benefiting from the idea and the results of the study for which the study of variables has not previously been studied in the Iraqi manufacturing environment according to researchers’ knowledge.